Study of the genus Ethmia Hübner, [1819] (Lepidoptera: Ethmiidae) from China, with descriptions of six new species - Zhu, Xiaoju; Wang, Shuxia (Zootaxa, 2022)
Six new species of Ethmia Hübner [1819] are described and illustrated from China: E. adunatimacula sp. nov., E. anfracta sp. nov., E. anomala sp. nov., E. corrugata sp. nov., E. rectiuga sp. nov. and E. transtimacula sp. nov. Two species (E. anatiformis Kun, 2001 and E. vietmiella Kun, 2001) are newly recorded for China; one species (E. crocosoma Meyrick, 1914) is newly recorded for the Mainland China. The male of E. susa Kun & Szabóky 2000 and the females of E. antennipilosa Wang & Li, 2004, E. vietmiella Kun, 2001 and E. yeni Kun, 2001 are reported for the first time. Images of adults and genitalia are provided.